2017
DOI: 10.1007/s40843-016-5151-6
|View full text |Cite
|
Sign up to set email alerts
|

Composite core-shell microparticles from microfluidics for synergistic drug delivery

Abstract: Microparticles have a demonstrated value for drug delivery systems. The attempts to develop this technology focus on the generation of featured microparticles for improving the function of the systems. Here, we present a new type of microparticles with gelatin methacrylate (GelMa) cores and poly(L-lactide-co-glycolide) (PLGA) shells for synergistic and sustained drug delivery applications. The microparticles were fabricated by using GelMa aqueous solution and PLGA oil solution as the raw materials of the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 39 publications
0
62
0
1
Order By: Relevance
“…One of the most widely used gelatin derivatives, gelatin methacrylate (GelMA) can be synthesized by reacting gelatin with methacrylic anhydride for introducing a methacryloyl substitution group on the reactive amine and hydroxyl groups of the amino acid residues (Figure C). Gelatin core–shell MPs with one or multiple GelMA cores and poly ( l ‐lactide‐ co ‐glycolide) (PLGA) shells were prepared to achieve coencapsulation and synergistic release of multiple drugs . Hydrophilic and hydrophobic drugs, doxorubicin, and camptothecine could be loaded into the core and the shell of the MPs, respectively, and then were released sequentially upon gradual degradation of the shell.…”
Section: Protein‐based Mpsmentioning
confidence: 99%
“…One of the most widely used gelatin derivatives, gelatin methacrylate (GelMA) can be synthesized by reacting gelatin with methacrylic anhydride for introducing a methacryloyl substitution group on the reactive amine and hydroxyl groups of the amino acid residues (Figure C). Gelatin core–shell MPs with one or multiple GelMA cores and poly ( l ‐lactide‐ co ‐glycolide) (PLGA) shells were prepared to achieve coencapsulation and synergistic release of multiple drugs . Hydrophilic and hydrophobic drugs, doxorubicin, and camptothecine could be loaded into the core and the shell of the MPs, respectively, and then were released sequentially upon gradual degradation of the shell.…”
Section: Protein‐based Mpsmentioning
confidence: 99%
“…Among them, microcarriers have emerged as novel biomimetic platforms, which offer 3D biomaterial scaffolds for cell encapsulation and aggregate formation [10][11][12][13][14][15]. Several approaches have been proposed for fabricating microcarriers, such as photolithography, micromolding, electrojetting and microfluidics [16][17][18][19][20][21][22][23][24]. In comparison with other approaches, microfluidic microcarriers are a promising technique for cell encapsulation because of their advantages of excellent monodispersity, precise size control, high throughput, and better microenvironmental control [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been proposed for fabricating microcarriers, such as photolithography, micromolding, electrojetting and microfluidics [16][17][18][19][20][21][22][23][24]. In comparison with other approaches, microfluidic microcarriers are a promising technique for cell encapsulation because of their advantages of excellent monodispersity, precise size control, high throughput, and better microenvironmental control [21][22][23][24][25][26][27][28]. However, because of the lack of effective nutrient exchange pathways, most of the microcarriers are restricted to a small size to avoid the formation of necrotic regions [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that GelMa inverse opal particles could be coupled with hemoglobin (Hb, the most important and commonly used oxygen‐carrying protein) via chemical bounding, and the combination between Hb and oxygen would be affected by the changing temperature caused via the photothermal response of MoS 2 , which indicated the controllable oxygen‐delivering capacity of these integrated microcarriers. In addition, it is worth mentioning that GelMa hydrogel has adjustable physical characteristics and great similarity to extracellular matrix, and thus GelMa is endowed with excellent biological properties . Because of the significant biocompatibility which is beneficial to cell proliferation, and the porous structure of the spherical 3D scaffold that provides physical supports for cell adhesion and growth, our desired microcarriers will certainly contribute to tissue repair.…”
mentioning
confidence: 99%